Arem wennu Raem (admiration or respect): A phenomenological understanding of Ilocano courtship - Suyat, Chase Mark; Angelie V. Salvador-Garcia, Mae; May N. Molina, Julie (Polaris Global Journal of Scholarly Research and Trends, 2023)
The study was conducted to determine the real meaning of "panagarem" in the concept of Ilocano and its evolution, ways, and practices through the years. This study employed phenomenology using individual interviews. There were 4 participants from each generation. The study revealed that panagarem” plays an essential role in understanding the deeper meaning of Ilocano courtship with new strategies in the courting of the Ilocanos, whether traditional or modern style. The custom of Ilocano panagarem requiring a certain man to work for the woman’s family was a “long, arduous, and expensive process of courting. A series of friendly dates is the normal starting point in the Ilocano way of courting, and it is usually beginning with “sinuron” or the process of teasing, a process of pairing off a potential couple. Moreover, material things are the basis of settling down, because they are focused on the idea of stability. However, some of the previous practices are not going away; they use them until now. However, some practices have been added because of technology and social media platforms. However, the bottom line here is that the respect and honor of the parents of the “Maarar-arem” are still practiced in different generations. That concludes that “Panagarem” is also “Panag- Raem.